Strategi Pengembangan Potensi Desa Dan Pemanfaatan Whatsapp Business Untuk Meningkatkan Nilai Ekonomi Bawang Merah Di Desa Srikayangan - Quita, Agnes Gracia (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Community service is expected to help the rural community or desa (village) where the service is located to develop better according to the potential that they have. The approach of our program is using online observation method and the data were obtained through internet. There are potential factors that should be maintained and preserved by Srikayangan Village in order to able to compete globally. Shallot is the most prospective commodity that the village should develop. The more the village is able to develop this commodity, the higher economic value will obtain. In order to do that, innovation required. Our program suggest to increase its economic value, shallots need to be develop into a product, shallot paste that can be used for basic seasoning or main seasoning. This innovation offers easiness and convenience to its consumer because they don’t have to peel, wash, nor blend shallots, they only have to buy the product and it will help them to cook faster. Marketing is one of the challenges that Srikayangan Village faces. We also offer assistance on how to market the product using Whatsapp Business because we believe digital media will be so much help. Whatsapp Business allows the seller to easily interact with their consumer. We expect that using Whatsapp Business will help Srikayangan Village to increase economic value of shallot. To be conclude, we hope that this program can help Srikayangan Village to earn more income by selling processed shallot products and using Whatsapp Business as a digital marketing medium.